The Performance Level of Shipping Signs and the Depth of Shipping Channels Contribute to Integrated Port Time with the Number of Ship Visits as a Moderating Variable - Rinandhi, Candra; Pahala, Yosi; Abidin, Zaenal; Sijabat, Eduard Alfian Syamsa (Amkop Management Accounting Review (AMAR), 2025)
In Indonesian seas, shipping signs' poor functionality might make it difficult for ships to navigate. Shipping accidents are more likely as a result, particularly when visibility is poor, like at night or in inclement weather. Analyzing the impact of shipping sign performance level and channel depth on the number of ship visits, the impact of shipping sign performance level, channel depth, and ship visitation on integrated port time, and the impact of shipping sign performance level and channel depth on integrated port time with the number of ship visits as a moderating variable are the goals of this study.The research methodology employed in this study is quantitative. A judgment sampling approach combined with a non-probability sampling technique was chosen by the researchers for this investigation. SPSS software was utilized by the researchers. The findings of the analysis indicate that both the channel depth and the level of performance of shipping signs have an impact on integrated port time. Additionally, the variable number of ship visits can moderate the relationship between the channel depth and integrated port time as well as the level of performance of shipping signs